How does the COVID-19 pandemic affect the preoperative evaluation and anesthesia applied for urinary stones? EULIS eCORE-IAU multicenter collaborative cohort study - Gökçe, Mehmet İlker; Yin, Shanfeng; Sönmez, Mehmet Giray; Eryıldırım, Bilal; Kallidonis, Panagiotis; Petkova, Kremena; Güven, Selçuk; Kiremit, Murat Can; de Lorenzis, Elisa; Tefik, Tzevat; Villa, Luca; Zeng, Guohua; et al. (Springer, 2020)
Stone disease is a unique condition that requires appropriate management in a timely manner as it can result in both emergent conditions and long term effects on kidney functions. In this study it is aimed to identify the up-to-date practice patterns related to preoperative evaluation and anesthesia for stone disease interventions during COVID-19 pandemic. The data of 473 patients from 11 centers in 5 different countries underwent interventions for urinary stones during the Covid-19 pandemic was collected and analyzed retrospectively. Information on the type of the stone related conditions, management strategies, anesthesiologic evaluation, anesthesia methods, and any alterations related to COVID-19 pandemic was collected. During the preoperative anesthesia evaluation thorax CT was performed in 268 (56.7%) and PCR from nasopharyngeal swab was performed in 31 (6.6%) patients. General anesthesia was applied in 337 (71.2%) patients and alteration in the method of anesthesia was recorded in 45 (9.5%) patients. A cut-off value of 21 days was detected for the hospitals to adapt changes related to COVID-19. Rate of preoperative testing, emergency procedures, conservative approaches and topical/regional anesthesia increased after 21 days. The preoperative evaluation for management of urinary stone disease is significantly affected by COVID-19 pandemic. There is significant alteration in anesthesia methods and interventions. The optimal methods for preoperative evaluation are still unknown and there is discordance between different centers. It takes 21 days for hospitals and surgeons to adapt and develop new strategies for preoperative evaluation and management of stones.
Keywords: COVID-19; SARS-CoV-2; Pandemic; Urolithiasis; Kidney Stones; Nephrolithiasis; Anesthesia